Anterior visual system involvement in non-Hodgkin's lymphoma. Issue 3 (March 1993) - Zaman, A G; Graham, E M; Sanders, M D
Abstract : Non-Hodgkin's lymphoma may have ocular involvement but optic nerve and chiasmal disease is unusual. Determining the cause of the neuropathy in this group of patients presents major difficulties despite modern neuroimaging and immunocytochemistry. Two patients with NHL are presented; one had an anterior chiasmal syndrome and the other bilateral optic nerve involvement. The first patient was thought to have lymphomatous infiltration and the second a concomitant infection (progressive multifocal leucoencephalopathy). Toxic effects of therapy were considered but finally rejected. The importance of modern neuroimaging and the role of optic nerve biopsy are discussed.